(untitled) (Molecular Medicine Communications, 2023)
Obesity and Type 2 Diabetes Mellitus (T2DM) have become the most prevalent public health issue around the world. The etiology of obesity and T2DM is multifactorial; with genes like Fat, Mass and Obesity-associated or FTO gene add to the complexity of the disease and diagnosis. Pakistan has recently been reported the highest prevalence of T2DM in the world. Since Pakistanis have a unique genetic disposition to T2DM due to the influence of genetic variations like rs9939609 in the FTO gene, as it is likely to be quantifiably different against the global genetic backdrop. A total of 300 participants were enrolled in this study, belonging to Dera Ismail Khan and Peshawar districts. Blood samples were collected from the enrolled patients following ethical approval and informed consent. HbA1c was used as a criterion for classifying non-diabetic controls, prediabetic, and diabetic patients. Patients’ anthropometric and demographic variables were recorded. Blood samples were subjected to both clinical chemistry and genetic analysis. Biochemically, samples were tested for HbA1c and lipid profile, whereas rs9939609 single nucleotide polymorphism (SNP) was assayed through direct sequencing. Demographic data showed that age and body mass index (BMI) were significantly higher in pre-diabetic and diabetic groups compared to the non-diabetic one. There was also statistically significant difference among the three groups in terms of their lipid profile parameters. Frequency of FTO-rs9939609 genotype distribution, however, was not significantly different in the three groups but patients with AA genotypes are 1.34 and 1.59 times more likely to develeop prediabetes and diabetes as compared to patients with TT genotypes. Lack of statistical association with FTO-rs9939609 SNP notwithstanding, our data reinforced the link between dyslipidemia, obesity and glycemic index.